2002
DOI: 10.1042/bj20020949
|View full text |Cite
|
Sign up to set email alerts
|

Acetaldehyde stimulates the activation of latent transforming growth factor-β1 and induces expression of the type II receptor of the cytokine in rat cultured hepatic stellate cells

Abstract: Acetaldehyde, the major active metabolite of alcohol, induces the activation of hepatic stellate cells (HSC), leading to over-production of alpha1(I) collagen and ultimately causing hepatic fibrosis. The underlying mechanisms of this process remain largely unknown. Transforming growth factor-beta1 (TGF-beta1) is a potent inducer of alpha1(I) collagen production. Accumulating evidence has shown a potential role for TGF-beta1 in alcohol-induced hepatic fibrogenesis. The aims of this study were to determine the e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
62
0
2

Year Published

2004
2004
2011
2011

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 77 publications
(66 citation statements)
references
References 47 publications
(99 reference statements)
2
62
0
2
Order By: Relevance
“…Kornek et al have clearly shown, that the addition of alcohol TAA further increases liver injury compared with TAA alone, although features of ALD such as steatosis, Mallory bodies, and "chicken-wire fibrosis" were missing (26). However, rodents are known to be notoriously resistant to fibrosis induction, and most models require addition of a second fibrosis trigger to alcohol administration (26,42); (b) the acetaldehyde concentration of 200 μmol/L causing significant CB1 upregulation in our study is approximately two-fold higher than hepatic concentrations typically encountered in human ALD, but still in the order of what has been described in experimental ALD after dosing rats with different amounts of alcohol (43)(44)(45)(46).…”
Section: Cb1mentioning
confidence: 68%
“…Kornek et al have clearly shown, that the addition of alcohol TAA further increases liver injury compared with TAA alone, although features of ALD such as steatosis, Mallory bodies, and "chicken-wire fibrosis" were missing (26). However, rodents are known to be notoriously resistant to fibrosis induction, and most models require addition of a second fibrosis trigger to alcohol administration (26,42); (b) the acetaldehyde concentration of 200 μmol/L causing significant CB1 upregulation in our study is approximately two-fold higher than hepatic concentrations typically encountered in human ALD, but still in the order of what has been described in experimental ALD after dosing rats with different amounts of alcohol (43)(44)(45)(46).…”
Section: Cb1mentioning
confidence: 68%
“…26 Cells were cultured in Dullbecco's modified Eagle's medium (DMEM) with 10% of fetal bovine serum (FBS). Semiconfluent HSC with 4-8 passages were used for experiments.…”
Section: Materials and Methods Materialsmentioning
confidence: 99%
“…26 Proteins were separated by SDS-PAGE with 10% of resolving gel, and transferred to PVDF membrane. Target proteins were respectively detected by primary antibodies against PPARg, phosphorylated types of PDGF-bR, EGFR, ERK1/2, JNK1/2 or AKT, and the corresponding non-phosphorylated types of total proteins; Bcl-2, Bax or cyclin D1, and subsequently by horseradish peroxidase-conjugated secondary antibodies (Santa Cruze Biotechnology, Santa Cruze, CA, USA).…”
Section: Western Blotting Analysesmentioning
confidence: 99%
“…Acetaldehyde was shown increase secretion of TGF-␤ by stellate cells and to increase expression of the type II TGF-␤ receptor (33). Neutralizing antibody to TGF-␤ decreased acetaldehyde-induced augmentation of the mouse ␣ 2 (I) collagen mRNA in stellate cells (13).…”
Section: The Activating Effect Of Acetaldehyde On Enhancing the Activmentioning
confidence: 99%